Covid-19 et passage éclair au distanciel pour les enseignants de langues vivantes du secondaire : une expérience renvoyant à l'irréductible présence en classe de langue - Emmanuelle Croze (Centre National d'Enseignement à Distance, 2021)
The period of quarantine linked to the Covid19 pandemic of the year 2020 has led secondary school foreign language teachers to move urgently from face-to-face to distance teaching. This unprecedented event has led them to experience, without any preparation, the loss of the crucial experiential element of the in-person classroom experience. This is what the results of our survey conducted during the period of quarantine show, particularly through the expression of a loss of contact with the students as experienced in the language classroom. The distance in this very particular situation underscored the lack of presence. But what does this presence mean for the 115 foreign language teachers who responded to our survey? Does the language teachers' definition of « presence » relate to the specific context of the language classroom? Or does it relate to the concept of presence as defined among scholars on technology-enhanced distance education?